Ocular manifestations of snake bites in a tertiary care hospital in rural Northern Kerala, India - George, Twinkle Ann; A. V., Asha; Ravindran, Risha; N. V., Latha (International Journal of Research in Medical Sciences, 2017)
Background: Snake bite is a neglected public health problem worldwide especially in the tropics. Studies on ocular manifestations are still fragmentary. The objective of the study was to find ocular manifestations among the snake bite cases with systemic envenomation admitted in the intensive care units in a tertiary care hospital in rural North Kerala, India during a period of 4 years from May 2012 to May 2016. Methods: It was a prospective, observational, cross sectional study. Institutional ethical committee approval was obtained for the study. A descriptive analysis of snake bite cases with systemic envenomation was done. Other snake bites are excluded from the study. Patients who needed ophthalmological opinion for ocular symptoms were analyzed. Results: Total suspected snake bites admitted in ICUs during the study period were 638. Only 7 patients (1%) with haematotoxic envenomation needed ophthalmological opinion for ocular symptoms. Patients in the present study ranged between the age of 11 and 53. Ocular lesions diagnosed among the 6 patients who developed capillary leak syndrome, were bilateral angle closure glaucoma in 3 patients, pan uveitis, disc edema and retinal haemorrhages in 2 patients, bilateral macular oedema. Youngest patient had intracranial haemorrhage and bilateral orbital hemorrhage, leading to exposure keratitis. SAV was administered in all patients ranging from 11-30 vials. All the patients except the patient with orbital haemorrhage had a grave prognosis. Still only one of these patients expired on day 3, rest all patients had better vision and survived due to timely management. Conclusions: A timely intervention especially at the initial presentation of capillary leak syndrome, can decrease the morbidity and save the life of a patient.